Mild cognitive impairment does not affect pattern electroretinogram in the elderly - a pilot study - Peng, Fun Swee; Norhani Mohidin,; Azzatul Ainur Mohd Kamal,; Zainora Mohammed,; Bariah Mohd-Ali, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of this study was to examine the effects of mild cognitive impairment on pattern electroretinogram (pERG) among urban elderly Malays. A total of 36 subjects aged 60 years and above comprising of 18 MCI subjects and 18 normal controls were recruited for this study. The inclusion criteria for both the MCI and normal subjects included best corrected distance visual acuity ≥ 6/9 (Snellen) with refractive error less than ±4.00 DS and/or ±2.00 DC (astigmatism), near visual acuity ≥ N8, absence or no previous history of any significant media opacities, retinal disorders and ocular pathologies. pERG was recorded with the RetiPort/Scan21 system in accordance with the International Society for the Clinical Electrophysiology of Vision standards. The target presented to subjects through a 19” CRT monitor was a black and white reversing checkerboard with luminance equal to 80 cd/m2, contrast 97% and stimulus frequency 2.00 Hz (4 rev/s). Amplitudes and implicit times of P50 and N95 waves generated by the system were noted and compared between the two groups. The results showed no significant difference in the amplitude and implicit times between the right and left eyes so only the right eye was used for comparison between the MCI and control groups. The mean amplitude and implicit times of the right eye of the MCI and control groups were 1.86±0.65 μV, 56.27±6.20 ms and 1.54±0.74 μV, 56.15±4.98 ms, respectively. T-test showed no significant differences in pERG amplitudes and implicit times between MCI and the control groups. In conclusion, our results may imply that the inner retina is intact in early MCI elderly subjects.